The role of mothers-in-law in antenatal care decision-making in Nepal: a qualitative study - Simkhada, Bibha (BioMed Central, 2010)
BACKGROUND: Antenatal care (ANC) has been recognised as a way to improve health outcomes for pregnant women and their babies. However, only 29% of pregnant women receive the recommended four antenatal visits in Nepal but reasons for such low utilisation are poorly understood. As in many countries of South Asia, mothers-in-law play a crucial role in the decisions around accessing health care facilities and providers. This paper aims to explore the mother-in-law's role in (a) her daughter-in-law's ANC uptake; and (b) the decision-making process about using ANC services in Nepal. METHODS: In-depth interviews were conducted with 30 purposively selected antenatal or postnatal mothers (half users, half non-users of ANC), 10 husbands and 10 mothers-in-law in two different (urban and rural) communities. RESULTS: Our findings suggest that mothers-in-law sometime have a positive influence, for example when encouraging women to seek ANC, but more often it is negative. Like many rural women of their generation, all mothers-in-law in this study were illiterate and most had not used ANC themselves. The main factors leading mothers-in-law not to support/encourage ANC check ups were expectations regarding pregnant women fulfilling their household duties, perceptions that ANC was not beneficial based largely on their own past experiences, the scarcity of resources under their control and power relations between mothers-in-law and daughters-in-law. Individual knowledge and social class of the mothers-in-law of users and non-users differed significantly, which is likely to have had an effect on their perceptions of the benefits of ANC. CONCLUSION: Mothers-in-law have a strong influence on the uptake of ANC in Nepal. Understanding their role is important if we are to design and target effective community-based health promotion interventions. Health promotion and educational interventions to improve the use of ANC should target women, husbands and family members, particularly mothers-in-law where they control access to family resources.